2021
DOI: 10.1111/jfpp.15474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro wet milling process on particle sizes, antioxidants, organic acids, and specific phenolic compounds of whole sea buckthorn ( Hippophae rhamnoides L.) juices

Abstract: Berries of sea buckthorn (SBT, Hippophae rhamnoides L.) is a deciduous shrub of the family Oleaster (Elaeagnaceae) which includes around 100 species in three genera generally found in the modest geographical latitudes of the Northern Hemisphere (Ciesarová et al., 2020;Li & Schroeder, 1996). SBT grows in mountainous regions of altitudes ranging from 2000 to 3600 m above sea level, having a high resistance in relation to temperature extremes between −45°C and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Furthermore, HPLC analysis of SBT juice revealed that higher amounts of low molecular weight organic acids and phenolic compounds were present in the MWM SBT juice than commercial type. The microbiological analysis showed that the initial total viable count of MWM SBT juice was within the permissible limit of standard [130].…”
Section: Particle Size Reductionmentioning
confidence: 92%
“…Furthermore, HPLC analysis of SBT juice revealed that higher amounts of low molecular weight organic acids and phenolic compounds were present in the MWM SBT juice than commercial type. The microbiological analysis showed that the initial total viable count of MWM SBT juice was within the permissible limit of standard [130].…”
Section: Particle Size Reductionmentioning
confidence: 92%
“…Finnish genotypes were in the middle, ranging from 4.2 to 6.5 g/100 mL, whereas Chinese genotypes showed the highest organic acid concentration, with values between 3.5 and 9.1 g/100 mL ( 37 ). It has been reported that sea buckthorn juice contains nine organic acids, namely quinic acid, L-malic acid, D-malic acid, succinic acid, pyruvic acid, tartaric acid, acetic acid, formic acid, and citric acid ( 38 ). Another study on six sea buckthorn varieties in Poland detected oxalic acid and isocitric acid ( 34 ).…”
Section: Nutrients and Bioactive Compoundsmentioning
confidence: 99%